Intellectual Capital, Corporate Governance and Firm Performance - Tsai, Jia-Hua; ., Shiow-Ying Wen (Information Management and Business Review, 2013)
This paper aims to exam the connection among intellectual capital, corporate governance and firm performance. Firm performance measured by Tobin’s Q is an important indicator. Business function such as R&D, advertising, and human resources, after adjusting for sales, remains important factors. Especially, management team should be aware of using leverage because excessive debt usage leads to poor Tobin’s Q. Investors should be cautious of capital structure when forming their investment portfolios. Although the influences of ownership structure on firm performance are not consistent, the effects are significant. Finally, whether there is independent director and the holdings ratio of board of director definitely affect the firm performance.